Atypical small bowel obstruction following repair of inguinal hernia: a case of intestinal stenosis of garré. - Weledji, EP; Nana, T; Aminde, L (Department of Surgery, UKM Medical Centre, 2013)
We here report an atypical case of small bowel obstruction ten days following repair of an inguinal hernia that had been recurrently reduced. A preoperative diagnosis of this rare intestinal stenosis of Garré is difficult, and was based on the clinical, operative and pathological findings. Forced reduction of a hernia is not recommended because of the risk of rendering its contents ischaemic with subsequent fibrotic stenosis, or reducing a strangulated bowel into the abdominal cavity with subsequent perforation and peritonitis.